Camel semen during breeding and non-breeding seasons - RAI, A K; SHARMA, N; MANIVANNAN, B; KHANNA, N D (The Indian Journal of Animal Sciences, 2013)
Camel semen production, evaluation and seminal characteristics during breeding and non-breeding seasons (hot humid and hot dry) have been reported. The colour, consistency,pH, sperm concertration, per cent live sperm and motility did not show much variation during different seasons. Sperm abnormalities increased during non-breeding season and the most predominant abnormalities were found in the mid-piece. Gel formation occurred immediately after ejaculation which liquified within 2 hr when kept at 37oC. The results are discussed in relation to sexual behaviour and hormaonal levels in the serum of the camel.